Resurgence of regional coalitions in Sarawak and Sabah since the federal elections of 2018 and 2022 - Arnold, Puyok; Hafizan, Mohamad Naim (Taylor & Francis (Routledge), 2023)
This article examines the resurgence of regional coalitions in Sarawak and Sabah following the 14th and 15th General Elections, respectively. It shows how federal-level government changes in Malaysia can result in the realignment of regional parties in Sarawak and Sabah, which had significantly shaped Malaysia’s political landscape as BN’s frontline states. The resurgence of the regional coalitions, Gabungan Parti Sarawak (GPS) and Gabungan Rakyat Sabah (GRS), demonstrates not only the fragmentation of national politics and the rise of regionalism but also the ease with which regional parties dominated by strongmen and aided by patronage can realign, enter and exit coalitions.